2007
DOI: 10.1364/ol.32.001578
|View full text |Cite
|
Sign up to set email alerts
|

Nanometer-thick Au-films as antireflection coating for infrared light

Abstract: The optical properties of ultrathin Au films on silicon have been studied in the infrared over a wide frequency range from 200 to 10,000 cm(-1). Thick films show a Drude behavior; i.e., with increasing frequency the transmission increases; for films below the percolation threshold at about 5 nm a negative slope for the frequency-dependent transmission is observed. When the thickness is further reduced, between 1 and 3 nm an anomaly occurs: the relative transmission reaches maximum values above 100% compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
21
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 13 publications
5
21
0
Order By: Relevance
“…However, there is restriction related to the percolation threshold. It depends on the method and temperature of growth and varies in a wide range from 1.5 to 10 nm [23][24][25]. For our simulations we have used the safe value of 10 nm as a minimum gold layer thickness.…”
Section: Plasmon Mode Management By Changing the Thickness Of Gold Anmentioning
confidence: 99%
“…However, there is restriction related to the percolation threshold. It depends on the method and temperature of growth and varies in a wide range from 1.5 to 10 nm [23][24][25]. For our simulations we have used the safe value of 10 nm as a minimum gold layer thickness.…”
Section: Plasmon Mode Management By Changing the Thickness Of Gold Anmentioning
confidence: 99%
“…The dielectric function also exhibits a monotonic increase in AC conductivity with wavelength, a clear signature that the film is above the percolation threshold [41,42]. The reported percolation threshold thickness for Au is 6.5nm with no adhesion layer [42,43]. The presence of Ti adhesion layer is expected to reduce the percolation thickness to a smaller value.…”
mentioning
confidence: 92%
“…In principle one can try to simulate semi-continues metal films with effective medium (EMA) theories 3,4 . However it was shown that EMA models fail to describe the dielectric properties of ultra-thin metal films 5,6 . In general this transition region was not yet studied in detail over a broad frequency range; nevertheless, these investigations should eventually provide the data to link the abrupt change in dc-conductivity with the observed shift of plasmon resonances in the visible.…”
Section: Introductionmentioning
confidence: 99%